Implementasi Pendidikan Kasih Di Dalam Keluarga Kristen - Munandar, Aris (Veritas Lux Mea (Jurnal Teologi dan Pendidikan Kristen), 2020)
Love education needs to be known, lived and practiced by everyone in community life, therefore the appreciation and practice of the teachings of Christ in accordance with the truth in the Bible, can really be practiced in daily life, specifically in the life of Christian families . Implementation of education and teaching of love, not only done in the church environment, the family as informal education, starting from the family, children are educated by parents, about education of gratitude that comes from the truth of the word of God, to seek back the meaning of values thank you education which is starting to erode. The influence of the times and the influence of globalization in an increasingly advanced and developing world, the role of parents is increasingly needed in relation to financial problems, attitudes and strengthening of children, making children in relationships with others who are not in accordance with teachings that are in accordance with the truth of God's Word. To overcome the smooth implementation of education and teaching in the family, the role of parents is needed in guiding children, to get their lives closer to God, through praying and reading the Bible regularly every day. Relationships between all families in the community are needed among the community to support each other, arrange harmony, avoid the nature of mutual arguments, stay away from jealousy, stay away from feelings of resentment and also improve harmony within the family and in the community he visits.